NOX2-dependent ATM kinase activation dictates pro-inflammatory macrophage phenotype and improves effectiveness to radiation therapy - Wu, Qiuji (Cell Death Differ, 2017)
Although tumor-associated macrophages have been extensively studied in the control of response to radiotherapy, the molecular mechanisms involved in the ionizing radiation-mediated activation of macrophages remain elusive. Here we show that ionizing radiation induces the expression of interferon regulatory factor 5 (IRF5) promoting thus macrophage activation toward a pro-inflammatory phenotype. We reveal that the activation of the ataxia telangiectasia mutated (ATM) kinase is required for ionizing radiation-elicited macrophage activation, but also for macrophage reprogramming after treatments with γ-interferon, lipopolysaccharide or chemotherapeutic agent (such as cisplatin), underscoring the fact that the kinase ATM plays a central role during macrophage phenotypic switching toward a pro-inflammatory phenotype through the regulation of mRNA level and post-translational modifications of IRF5. We further demonstrate that NADPH oxidase 2 (NOX2)-dependent ROS production is upstream to ATM activation and is essential during this process. We also report that the inhibition of any component of this signaling pathway (NOX2, ROS and ATM) impairs pro-inflammatory activation of macrophages and predicts a poor tumor response to preoperative radiotherapy in locally advanced rectal cancer. Altogether, our results identify a novel signaling pathway involved in macrophage activation that may enhance the effectiveness of radiotherapy through the reprogramming of tumor-infiltrating macrophages.